Creative Thinking in Digital Media Art Design Education - Dominguez Chan (CV TOPAZART, 2022)
The study on the brain mechanism of creativity mainly has two aspects: the creative thinking process and the brain structure and functional connection characteristics of highly creative people. Human’s rational thinking mode has a high degree of freedom and transcendence, and such problems cannot be expected to be studied by elaborating on the realization of the nervous system. The rational thinking of the brain is mainly based on the structured thinking mode, and the structured thinking mode shows great scientific power. This paper studies the theoretical model of innovative thinking based on category theory, analyzes the creation process of two scientific theories, landmarks in the history of science, and provides an intuitive, transparent interpretation model and rigorous mathematical argument for creative thinking. The structured thinking method has a great revelation and helps create new scientific theories.